Porphyrin-based porous organic polymers enriched with Fe3O4 nanoparticles as electrosensors for the detection of endocrine disrupting chemicals in water - Nombona, Nolwazi (University of Pretoria, 2024)
Dissertation (MSc (Chemistry))--University of Pretoria, 2023.